Population Size Effects on Progeny Performance in Banksia ilicifolia R. Br. (Proteaceae) - BAMBANG HELIYANTO; TIANHUA HE; HANS LAMBERS; ERIK J. VENEKLAAS; SIEGFRIED L. KRAUSS (Bogor Agricultural University, Indonesia, 2009)
A reduction in population size due to land clearing and habitat fragmentation may have negative effects on plant fitness. A relationship between population size and progeny performance for four small (n < 20 plants) and four large (n > 100 plants) populations of Banksia ilicifolia, a widespread but naturally fragmented species in south-western Australia, was assessed. Seeds collected from the field were germinated and a comparative growth study conducted in a greenhouse. After six months, the survival rate of seedlings from larger populations was double (36%) that of smaller populations, while germination rates and other measures of growth performance were independent of population size. The conservation and management implications of reduced fitness associated with small population size in B. ilicifolia are discussed. Key words: population size effect, fragmentation, Banksia ilicifolia, growth study